혼합엔트로피 제어에 따른 단일 FCC 고용체 합금의 물성변화 분석 - 이제인; Je In Lee; 오현석; Hyun Seok Oh; 김준혁; Jun Hyuk Kim; 박은수; Eun Soo Park (대한금속·재료학회지, 55(1), 2017)
In the present study, we systematically investigated the effect of entropy of mixing (ΔS mix ) on the mechanical and thermal properties of single phase FCC solid solutions with multi-principal elements. An increase in ΔS mix led to an increase in micro-hardness and a decrease in thermal conductivity (κ) due to severe lattice distortion. Furthermore, NiCoFeCrMn high-entropy alloy (HEA) exhibited the highest κ 1 /κ e ratio of ~1.13, because with increasing ΔS mix the reduction in lattice thermal conductivity (κ 1 ) was less than that of electron thermal conductivity (κe). In particular, a crossover in the properties` variation was noticeable at a specific ΔS mix of ~8.3±0.3 J/mol·K, which means the properties of single phase FCC solid solutions can be optimized by modulating ΔS mix . The results can provide a guideline for manipulating the properties of single solid solutions using the HEA design concept, and help develop novel materials with optimal properties that are usable in extreme environments. (Received June 7, 2016; Accepted July 20, 2016)